Thoughts papers on mind, meaning, and modality - Yablo, Stephen (Oxford : Oxford University Press, 2008)
In 12 essays Stephen Yablo presents a modern-day examination of Cartesian themes in the metaphysics of mind, including mental/physical dualism, the possibility of disembodied existence, conceivability as a guide to possibility, and the nature of solipsistic content.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy of mind; Mind and body; Causation